Comprehensive Chemical Profiling and Mechanistic Insight into Anticancer Activity of Annona muricata Leaves Extract - Rehab H. Abdallah; Al-sayed; Youssef M. Shehata; Doaa M. Abdel-Fattah; Rahnaa M. Atta; Omer I. Fantoukh; Ahmed M. Mustafa (MDPI AG, 2024)
The aqueous extract of Annona muricata L. leaves was thoroughly analyzed using the UPLC-MS/MS, in addition to a new approach of examination of the extract's impact on cancer of EAC(Ehrlich ascites carcinoma) in albino male mice. The aim was to investigate the diversity of the phytochemical constituents of the aqueous leaf capsule extract and their impacts on EAC as anticancer agents. The UPLC-ESI-MS/MS screening resulted in 410 tentatively identified metabolites. Among them, 384 compounds were tentatively identified in a previous study, besides a number of 26 compounds belonging to acetogenins, phenolics, flavonoids, alkaloids, and other miscellaneous compounds, which were exclusively identified in the aqueous extract of the leaf capsule. Interestingly, a new compound was tentatively characterized as galloyl-quinic acid-rutinoside. This study also demonstrated that treating EAC mice with an extract from A. muricata leaves significantly improved the abnormalities in the expression of pro-apoptotic (Bax and caspase-3) and anti-apoptotic (Bcl-2) genes. Furthermore, the extract showed good protection against induced Ehrlich hepatocarcinoma, according to the microscopical, histological, and immune-histochemical analyses of the liver tissues and tumor mass.